Basic inertial quantities including multi-segment trunk of fit, young males obtained based on personalized data. (9th June 2020) - Erdmann, W.S.; Kowalczyk, R.
Abstract: Up to now several researchers use values of basic inertial quantities of human body parts obtained for old cadavers. Taking into account the trunk researchers presented this body part often as one segment only and rarely as few-segment part. The purpose of this study was obtaining values of basic inertial quantities of body parts including five parts of the trunk for young, fit living males. Thirty young, fit males (age: 24 ± 4 years, height: 179 ± 6 cm, body mass: 74 ± 7 kg) were directly measured (circumferences and skin-fat folds) and photographed in order to use these data for Clauser et al. (parts of extremities) and Erdmann's (parts of trunk) methods for estimation of mass and location of centres of mass of body parts. These methods take into account personal data for estimating inertial quantities. Relative mass (according to the mass of the whole body) of trunk parts (sum of thorax + abdomen + pelvis but without shoulder girdle) of subjects investigated in this work was similar to that obtained by Dempster for old cadavers. Relative mass differed for shoulders and for lower extremities. Old subjects for both lower extremities had around 31–32% of the whole body mass and young subjects had almost 37%. Procedure for obtaining location of the whole body centre of mass for graphical method (summation of mas) was presented. Obtained data are very important for analyses of arched trunk, e.g. in high jumping, pole vault jumping, rhythmic gymnastics of young, fit athletes and also for models of young passengers in car-crash tests, for ergonomics and medical analyses and other purposes.